Succeeding in Aging Research During the Pandemic: Strategies for Fellows and Junior Faculty. Issue 1 (13th October 2020) - Cohen, Andrew B.; Parks, Anna L.; Whitson, Heather E.; Zieman, Susan; Brown, Cynthia J.; Boyd, Cynthia; Covinsky, Kenneth E.; Steinman, Michael A.
Abstract : Fellows and junior faculty conducting aging research have encountered substantial new challenges during the COVID‐19 pandemic. They report that they have been uncertain how and whether to modify existing research studies, have faced difficulties with job searches, and have struggled to balance competing pressures including greater clinical obligations and increased responsibilities at home. Many have also wondered if they should shift gears and make COVID‐19 the focus of their research. We asked a group of accomplished scientists and mentors to grapple with these concerns and to share their thoughts with readers of this journal. Abstract : See related Special article by Storer et al .